Orthopedic Treatment in the Era of COVID-19: Perspectives from a National Survey in Thailand - Jianmongkol, Surut; Sukhonthamarn, Kamolsak; Vinitpairot, Chaiyos (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: The coronavirus disease 2019 (COVID-19) pandemic has affected the management of patients with non-emergent orthopedic conditions, resulting in postponed surgical intervention(s) and changes in hospital services. Specific guidelines have been issued for emergency orthopedic cases; however, no definitive guidelines have been proposed for the management of elective or non-urgent conditions during the pandemic. As such, physicians have been obliged to make decisions based on their judgment. This study aimed to analyze data regarding changes in general orthopedic practices during the pandemic, especially those pertaining to surgery, clinical procedures, follow-up periods, referrals, and protective equipment. Methods: This study investigated the impact of the COVID-19 pandemic on the management of non-urgent orthopedic conditions by outpatient orthopedists. A questionnaire was developed and shared with nationwide orthopedic social media groups and through e-mails. Results Of the 200 orthopedic surgeons invited to participate, 129 (64.5%) responded. Results revealed that 65.9% of the surgeons preferred conservative treatment to surgery among patients with the appropriate indications. Additionally, follow-up periods were extended in 69.0% of patients, and 70.5% were prescribed more medication. The N-95 mask and home delivery system for medications were the two most desirable protective equipment and innovations that surgeons needed (79.1% and 69.8% of respondents, respectively). Conclusions: The COVID-19 pandemic has led to changes in general orthopedic practices in outpatient clinics, such as a preference for more conservative treatment than surgery, extension of appointment periods, prescription of medicine for a longer period, and use of drug delivery to patients’ homes.